Diversity and Abundance of Aquatic Insect Fauna in an Urban Freshwater Lake, Hatirjheel, Dhaka, Bangladesh (Bangladesh Journal of Zoology, 2023)
Freshwater lakes are a crucial component of the urban ecology and offer several direct and indirect advantages to its people. Habitat degradation of native insects has happened because of development activities and unscientific natural resource management. As a consequence, many insects of freshwater lakes are now rare and endangered. A research was conducted to find out the abundance, variety and distribution of aquatic insect fauna in an urban freshwater lake, Hatirjheel, Dhaka during November 2015 to February 2016. A total of 3255 individuals of water insects comprising of 11 species and 31 genera under 20 families belonging 5 orders were recorded. The order Hemiptera contained the highest abundance (38.71%) including 7 families and 12 genera containing 5 species, while Trichoptera had the lowest (6.45%) including 2 families and 2 genera. The dominating species in the lake was Micronecta haliploides. The maximum 19 aquatic insect species were reported in the lake's vegetation-rich section near the Mouchak-Moghbazar flyover (Spot 1), whereas a minimum of 5 species were found near the Modhubagh bridge road (Spot 2). Species diversity index (H′ = 2.74), species richness (SR = 8.54), aquatic insect distribution evenness (J′ = 0.80), community dominance (CD = 46.94%), and Simpson’s index (λ = 0.17) were analyzed in this study to determine the diversity, abundance, distribution and dominance of aquatic insect fauna in this lake.Bangladesh J. Zool. 50(3): 363-372, 2022